2018
DOI: 10.1007/978-3-030-03189-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Resilience – An Introduction

Abstract: Resilience has become an important topic on the safety research agenda and in organizational practice. In this chapter we give an introduction to the research area and some of the current challenges, before we present the aim of the book.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“… 23 The role of various contextual factors (eg, regulatory systems, cultural and organisational factors, leadership) remains relatively unexplored and in need of investigation and theorising. 30 36 …”
Section: Introductionmentioning
confidence: 99%
“… 23 The role of various contextual factors (eg, regulatory systems, cultural and organisational factors, leadership) remains relatively unexplored and in need of investigation and theorising. 30 36 …”
Section: Introductionmentioning
confidence: 99%
“…However, while most current research on Safety-II addresses activities of front-line workers and clinical leadership, the role of external regulatory systems is hardly addressed. 3 The relationship between regulation and Safety-II and the role regulators could play in improving or undermining Safety-II performance, needs investigation and theorising. 4 5 In this article, we combine theory with practice examples to show how Safety-II principles could influence the interactions between healthcare providers and their regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these, there has been a slow adoption of RE across the general industry. Most of these studies are too abstract and general [13], and there is no uniformly accepted definition of RE [9,10,[14][15][16], with recent reviews suggesting five to ten different but inter-related explanations [9,10]. Boring [15,16] argued this was because it existed more as a conceptual framework, while Sheridan [14] suggested that it reflected a family of ideas.…”
Section: Introductionmentioning
confidence: 99%
“…While these provide a rich source of information about selected aspects of RE, most of these studies failed to build on each other's work, so there is very little shared analytical framework [10,21]. This suggests that RE is ill-defined, and it is unclear which phenomena are to be operationalized for organisational safety [9,13]. These are significant gaps which can hinder efforts in benchmarking RE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation